Training courses in risk assessment methodologies: uncertainty analysis, weight of evidence assessment and assessment of biological relevance. Issue 7 (19th July 2022) - Beronius, Anna; Craig, Peter; Hanberg, Annika; Hart, Andy; Sahlin, Ullrika; Zilliacus, Johanna
Abstract: This report summarises the trainings delivered under the contract OC/EFSA/SCER/2017/01‐Lot 3. The objective of the trainings was to support understanding, uptake and implementation on the following EFSA Guidance: 1) Guidance on Uncertainty Analysis in Scientific Assessments, 2) Guidance on the use of the weight of evidence approach in scientific assessments and 3) Guidance on the assessment of the biological relevance of data in scientific assessments. In total, 14 trainings were organised: eight on uncertainty and six on weight of evidence and biological relevance. Several modalities were used for the trainings including face‐to‐face training, online synchronous training, e‐learning, webinars, a workshop and a tutorial video. The trainings had in total 630 participants from EFSA's Scientific Committee and Panels, EFSA working groups, EFSA Networks, EFSA staff, risk managers from DG SANTE and member state authorities and risk assessors from member state authorities. The trainings received very good feedback from the participants with a mean value of 4.3 of 5 possible for the concluding question in the feedback questionnaire: "Overall, are you satisfied with the course?".